Ocular Myiasis in a Nigerian Adolescent: A Case Report - Bodunde OT; Onabolu OO; Amoo AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2015)
Ocular myiasis is a rare condition with varying consequences, from mild to life threatening condition. This case of ocular myiasis is presented to highlight the challenges in making a clinical diagnosis. The study is a case report of a 16-year old female pupil who presented with five months history of "extrusion of worms" from her left eye. An initial assessment of loasis was made until she brought a sample of what she called "worms." Laboratory examination of the specimen using a magnifying glass revealed a larva. The girl was treated conservatively with a combination of topical antibiotic and topical non-steroidal anti-inflammatory drugs after trimming the eyelashes. On immediate follow up, the girl had no residual visual challenges. Although ocular myiasis is rare, a high index of clinical suspicion is required and myiasis should be considered a differential diagnosis of loasis.